A Prospective Hospital-Based Study on Cutaneous Manifestations in Patients with Polycystic Ovarian Syndrome (PCOS) - Kumar, Abhishek; Udayan, Uday Kumar (Student's Journal of Health Research Africa, 2024)
Background: Polycystic Ovarian Syndrome (PCOS) is a common endocrine disorder among women of reproductive age and is often associated with distinct cutaneous manifestations such as acne, hirsutism, and acanthosis nigricans. These dermatological signs can serve as early clinical indicators of underlying hormonal and metabolic disturbances. Aim: To evaluate the frequency and pattern of cutaneous manifestations in PCOS patients and assess their association with body mass index (BMI) in a tertiary care setting. Methods: A prospective observational study was conducted over a period of 6 months at a tertiary care hospital in North Bihar. Fifty female patients aged 15–45 years, diagnosed with PCOS based on the Rotterdam criteria, were included. Data on demographic details, BMI, and various cutaneous manifestations were collected using a structured proforma. Severity grading tools such as the Ferriman-Gallwey score for hirsutism and the Global Acne Grading System (GAGS) for acne were utilized. Statistical analysis was performed using SPSS version 23.0. Results: The mean age of participants was 24.8 ± 4.3 years, with 68% being overweight or obese. Acne was the most common manifestation (80%), followed by hirsutism (64%) and acanthosis nigricans (48%). Androgenic alopecia, seborrhea, and striae distensae were also observed. A statistically significant association was found between elevated BMI and the presence of acanthosis nigricans (p = 0.012) and hirsutism (p = 0.034). Conclusion: Cutaneous manifestations are highly prevalent among women with PCOS, with acne and hirsutism being the most common. These features can serve as valuable clinical markers for early identification of PCOS, particularly in dermatology settings. Recommendations: Routine dermatological screening in women with suggestive symptoms should be encouraged to facilitate early diagnosis and management of PCOS. Weight management and lifestyle interventions should be emphasized in overweight patients to mitigate dermatological and metabolic complications.